2020
DOI: 10.1155/2020/9418475
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Infection and Its Determinants among Pregnant Women in Ethiopia: A Systematic Review and Meta-Analysis

Abstract: Background. Hepatitis B virus (HBV) is an infectious and a global public health problem. The prevalence of HBV infection among pregnant women is between 2.3% and 7.9%. HBV infection during pregnancy is associated with prenatal transmission to the fetus. HBV has an effective vaccine which reduces up to 96% of the transmission. Although different studies were conducted in Ethiopia, none of them showed the national prevalence of HBV infection among pregnant women. Therefore, this study was conducted to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 61 publications
0
14
1
Order By: Relevance
“…The prevalence was the highest across the country compared to the pooled prevalence as showed by 26 recently. Previous studies in different regions of Ethiopia reported lower proportions, from the lowest prevalence (3.7%) in Jimma town to the highest (8.4%) in Dire Dawa.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The prevalence was the highest across the country compared to the pooled prevalence as showed by 26 recently. Previous studies in different regions of Ethiopia reported lower proportions, from the lowest prevalence (3.7%) in Jimma town to the highest (8.4%) in Dire Dawa.…”
Section: Discussionmentioning
confidence: 76%
“…32 In this study area, the overall sero-prevalence of HBsAg among pregnant women was 9.2%, which could be considered as a high endemicity area (with sero-positivity ≥8% seropositive), based on WHO classification criteria of endemicity of HBV infection. 13 The prevalence was the highest across the country compared to the pooled prevalence as showed by 26 recently. Previous studies in different regions of Ethiopia reported lower proportions, from the lowest prevalence (3.7%) in Jimma town to the highest (8.4%) in Dire Dawa.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…10,19 A meta-analysis conducted in Ethiopia also reported a positive association between multiple sexual partners and HBV infection. 22 The association between these two variables shows that women need to take necessary care including limiting the number of sexual partners/one to one sexual practice and increasing condom use behavior so as to minimize/avoid the chance of contracting HBV.…”
Section: Discussionmentioning
confidence: 99%
“…The pooled prevalence for HBV among pregnant mothers in Ethiopia was 4.75% [30]. Different factors, such as having a history of blood transfusion, history of use of sharp materials, having multiple sexual partners, ear pricing, history of abortion, place of delivery, the practice of female genital mutilation, history of tooth extraction, cesarean section, and tattooing, were some of the major risk factors associated with HBV Ag seropositivity in previous studies in similar settings [23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 97%